Barney in space - Clark, Margaret Goff.; Lewin, Ted (New York Dodd, Mead, 1981)
Although several of his friends try to prevent it, Barney is transported to the moon where Rokell, a dangerous Gark from the planet Ornam, awaits him.
Keywords: Extraterrestrial beings -- Fiction; Space flight to the moon -- Fiction